Wiegand's metalexicography as a framework for multilingual, multicultural, explanatory music education dictionary for South Africa - Smit, Maria (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Litt) -- University of Stellenbosch, 1996.